Modeling and Technical Analysis of a Modified Z-Source Converter for Driving a Three-Phase Induction Motor: Modified Z-Source Converter for Three-Phase Induction Motor - Shami, Umar Tabrez; Lohdi, Zeeshan (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2021)
A modified Z-source converter to boost DC voltage is proposed. The modification has been proposed by engaging an additional power switching device in parallel connection to the conventional Z-source converter. The effectiveness of the additional power switching device in the Z-source converter is demonstrated and discussed in detail. For calculations, a mathematical model of the proposed modified Z-source is also presented. For experimental demonstration the proposed modified Z-source converter is connected to an independent three-phase DC-to-AC three-phase inverter. The load on the modified Z-source converter with a three-phase inverter is a three-phase induction motor. As shown in this paper, the three-phase inverter will play no role boosting the DC voltage. Two wellknown PWM switching schemes have been implemented on the three-phase inverter. The proposed modified Z-source converter successfully boosts the DC voltage; in addition, it is shown that the DC output voltage settling time varies with the PWM modulation index.